2018
DOI: 10.1007/s00784-018-2528-5
|View full text |Cite
|
Sign up to set email alerts
|

What kind of third molars are disease-free in a population aged 30 to 93 years?

Abstract: Our results suggest that the number of disease-free third molars decreased with increasing age, and most dramatically, this occurred among teeth at cervical level with the neighboring second molar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…Our findings showed that from the third molars in adults aged ≥30 years, 37.1% were impacted and 3.6% were horizontally located (Table ). Furthermore, our recent study on the same material documented that 39.6% of the mandibular third molars are located close to the mandibular canal . If these teeth require extraction, it would be easier in younger than in older persons.…”
Section: Discussionmentioning
confidence: 92%
“…Our findings showed that from the third molars in adults aged ≥30 years, 37.1% were impacted and 3.6% were horizontally located (Table ). Furthermore, our recent study on the same material documented that 39.6% of the mandibular third molars are located close to the mandibular canal . If these teeth require extraction, it would be easier in younger than in older persons.…”
Section: Discussionmentioning
confidence: 92%
“…Staderini et al in their recent systematic review concluded that there was no sufficient evidence to define absolute indications or contraindications for preventive removal of impacted third molars [28]. Ventä et al found that the number of disease-free third molars decreased with increasing age, and most dramatically, this occurred among teeth at the cervical level with the neighboring second molar [29]. Only one-fourth of third molars may remain disease-free after the age of 30 years [29].…”
Section: Discussionmentioning
confidence: 99%
“…Ventä et al found that the number of disease-free third molars decreased with increasing age, and most dramatically, this occurred among teeth at the cervical level with the neighboring second molar [29]. Only one-fourth of third molars may remain disease-free after the age of 30 years [29]. It is also important not to forget that positional changes and eruption of ITM are an unpredictable phenomena [30].…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of M3s is generally believed to increase the residual periodontal pockets and caries risks of M2s [24,26,28], the decision on preventive extraction of asymptomatic M3s is hard for dentists and patients [17,29]. Even in most studies, the preventive extraction of M3s can be benefit for the health of neighboring M2s [11,13,14], in many clinical situations, asymptomatic M3s are indeed more likely retained until irreversible damages happen [15,16].…”
Section: Discussionmentioning
confidence: 99%